Powtoon-Based Animated Video Media Development on Subtheme 3 Humans And Objects In Their Environment - Ikbal Aldian Tawakal; Nurlinda Safitri; Rini Sri Indriani; Resyi A. Gani (Journal of International Multidisciplinary Research, 2025)
The development of this animated video media is based on the problems found at SD Negeri Singajaya 01 Bogor Regency. Starting from students not getting innovative learning media, and still using conventional methods in the learning process so that technology in learning is still very lacking. The purpose of this research is to develop powtoon-based animated video media in class V subtheme 3 humans and objects in their environment and determine the feasibility of powtoon-based animated video media with validation tests by material experts, media experts, and linguists, as well as student responses. The experimental subjects were fifth-grade elementary school students. The development of this video media uses the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The results of the validation test by material experts showed a percentage value of 88% in the very feasible category, media experts gave a percentage value of 100% in the very feasible category, and linguists gave a percentage value of 60% in the feasible category with revisions. The student response based on the questionnaire shows a positive response with a percentage score obtained of 91% in the category of very feasible, student response. The results can be concluded that the development of powtoon-based animated video media on subtheme 3 of humans and objects in their environment is suitable for use and motivates teachers and students in the learning process.